Disability Inclusion in Nigeria : A Rapid Assessment - World Bank (World Bank, Washington, DC, 2020)
According to the World Health Organization, in 2018, about 29 million of the 195 million people who comprise Nigeria’s national population were living with a disability. Data from the 2018 Nigeria Demographic and Health Survey reveal that an estimated 7 percent of household members above the age of five (as well as 9 percent of those 60 or older) have some level of difficulty in at least one functional domain, seeing, hearing, communication, cognition, walking, or self-care; and 1 percent either have a lot of difficulty or cannot function at all in at least one domain. These estimated rates, while significant, are probably even higher because currently available data likely underestimate the prevalence. This rapid social assessment was undertaken to document the current socioeconomic status of persons with disabilities in Nigeria. Findings indicate that persons with disabilities lack access to basic services and that attitudinal barriers represent a major impediment to their socioeconomic inclusion. Inclusive policies are either nonexistent, weak, or inadequately implemented. There is an urgent need to improve the current socioeconomic situation of persons with disabilities in Nigeria.